Lagrangian pathways under the Filchner-Ronne Ice Shelf and in the Weddell Sea - Maderich, V.; Bezhenar, R.; Brovchenko, I.; Bezhenar, A.; Boeira Dias, F.; Uotila, P. (Ukrainian Antarctic Journal, 2022)
The study’s objective is to construct Lagrangian pathways under the Filchner-Ronne Ice Shelf (FRIS) and in the Weddell Sea using the data of numerical simulation of currents and Lagrangian numerical methods. The results of modeling the circulation, temperature, and salinity in the Weddell Sea and the FRIS cavity from the Whole Antarctica Ocean Model were used to run the particle-tracking model (Parcels) for computing Lagrangian particle trajectories. The basic version of the Parcels model does not have an option for particle reflection from the solid boundaries, including the ice shelf. Therefore, the corresponding kernel was used in the study. To avoid errors in interpolation near the solid boundary when the model algorithm cannot find enough grid nodes around the particle, the function of particle recovery was implemented. To analyze the movement variations of the water masses under the FRIS, a set of particles was released in the Ronne Depression near the ice shelf front. Simulation continued for 20 years of particle movement. Particles were released at two depths: 350 m and 500 m, every 4 hr within the first 365 days. To characterize the redistribution of water masses, we calculated the ‘visitation frequency’, i.e., the percentage of the particles that visited each 2 × 2 km grid column at least once in a modeling period. The mean age of visits was also calculated to characterize the age of water masses. The results of this analysis generally agreed with schemes based on water mass analysis. The released particles first move southward along the Ronne Trough. The flow then turns to the east, reaching the passage between Berkner Island and Henry Ice Rise after three years. After ten years, the released particles reach the Filchner Trough, through which water flows out to the shelf of the southern part of the Weddell Sea. Over time, the particles penetrate all parts of the cavity. The particles also cross the Ronne Shelf front and are carried away by currents on the Weddell Sea shelf. In 20 years, almost the same number of particles left the cavity through the Ronne ice front (43%) and the Filchner ice front (37%), whereas the rest of the particles (20%) remained under FRIS.